EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI REGRESI LINIER - Wulansari, Andhita Dessy (IAIN Ponorogo, 2014)
Abstract; in general, learning statistics in class do not working at all, active lecturer predominate and student tend to passive as good hearer. Conventional study like this, make student only memorizing and working procedure without comprehend concept in fact. According to Hudojo,